Breaking invisible walls: American Corners’ programmes and strategies for strengthening interreligious dialogue and inclusive peace - Solemos, Roana Marie Flores (Animo Repository, 2024)
The main agenda of this study is to explore the various programmes and strategies of American Corners in Mindanao to amplify interreligious dialogue and peacebuilding within their communities. The researchers utilized the virtual focus group discussion approach, and the data collected was analysed using Braun and Clarke’s six-phase reflexive thematic analysis model. The researchers uncovered the creative efforts of each American Corner, integrating themes of interreligious dialogue, peace, mental health and animal welfare. The communities’ evolving needs greatly influence programming, with strong partnerships and immersive learning sessions cited as key programme highlights among the American Corners. However, poor infrastructure – particularly poor Internet access and power interruptions – poses significant challenges, prompting a focus on in-person over hybrid and virtual events. The recommendations include improving information accessibility and dissemination, fostering strategic partnerships, and deepening community engagement to sustain peace efforts in Mindanao.